2022
DOI: 10.1097/mcg.0000000000001777
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Versus Frozen Versus Lyophilized Fecal Microbiota Transplant for Recurrent Clostridium Difficile Infection

Abstract: Introduction: Clostridium difficile Infection is a significant source of morbidity and mortality, which is on the rise. Fecal Microbiota Transplantation (FMT) is an alternative therapy to antibiotics with a high success rate and low relapse rate. Current data regarding the efficacy of the types of FMT used, namely fresh, frozen, and lyophilized is conflicting. Our review attempts to consolidate this data and highlight the most efficacious treatment currently available.Methodology: MEDLINE, Embase, Web of Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Another recent network meta-analysis further supports the use of frozen or lyophilized stool for FMT. While there appears to be a marginal decrease in relative efficacy (fresh FMT: 93% efficacy [95% CI: 0.913 to 0.999]; frozen FMT: 88% efficacy [95% CI: 0.857 to 0.947]; lyophilized FMT: 83% efficacy [95% CI: 0.745 to 0.910]), this slight reduction seems to be outweighed by the accessibility and practicality of frozen or lyophilized preparations [32].…”
Section: Fmt As a Successful Intervention For Preventing Rcdimentioning
confidence: 99%
“…Another recent network meta-analysis further supports the use of frozen or lyophilized stool for FMT. While there appears to be a marginal decrease in relative efficacy (fresh FMT: 93% efficacy [95% CI: 0.913 to 0.999]; frozen FMT: 88% efficacy [95% CI: 0.857 to 0.947]; lyophilized FMT: 83% efficacy [95% CI: 0.745 to 0.910]), this slight reduction seems to be outweighed by the accessibility and practicality of frozen or lyophilized preparations [32].…”
Section: Fmt As a Successful Intervention For Preventing Rcdimentioning
confidence: 99%
“…Prolonged frozen storage leads to an increase in Firmicutes to Bacteroidetes ratio, as some Gram-negative species are depleted during storage and some hypothesize that trials in which frozen FMT was found to be effective also depend on this phenomena of selective depletion of administered Bacteroidetes . A network metaanalysis of 8 studies in patients with recurrent C. difficile infection (CDI) found similar efficacy in fresh versus frozen FMT (93% vs. 88%, P = 0.18) and concluded that the trend towards improved efficacy with fresh FMT was offset by safety, accessibility, and practicality of frozen FMT [ 54 ]. Similar findings have been observed in UC from meta-analyses of 22 studies where the efficacy of fresh (34.4%) versus frozen (46.8%) was similar [ 55 ].…”
Section: Procedure-related Factors and Outcome Determinants In Fmtmentioning
confidence: 99%
“…Meta-analyses have shown that, among these, colonoscopy is the most effective mode of delivery, with no significant differences compared to oral administration (> 80% overall) [132,137,138] . Importantly, the upper delivery method has shown additional advantages in treating immune-related disease, likely due to immune regulation in the small intestine [127,139] .…”
Section: New Formulations/strategiesmentioning
confidence: 99%
“…Because the microbiome plays a key role in modulating the immune system, FMT treatment is being tested in an array of immune-related diseases, ranging from acute graft-versus-host disease (GVHD) to Type I diabetes or Multiple sclerosis, with variable but again promising results, especially in the treatment of GVHD [14,139] . Increasing data demonstrate that the ability of the gut microbiome to metabolize xenobiotic compounds and to regulate immune responses has profound consequences for anticancer therapies [15,31,53] .…”
Section: New Disease Targetsmentioning
confidence: 99%
See 1 more Smart Citation